Pengembangan Model Pembelajaran Berbasis Sains untuk Anak Usia Dini - Zurqoni, Zurqoni; Hariyanie, Ida (SYAMIL, 2018)
This research is a type of research and development. The development model used through the adaptation results from the Borg and Gall models. In this study carried out only with 8 stages: 1) Potential and Problems; 2) Information Collection; 3) Product Design; 4) Design Validation; 5) Design Revision; 6) Product Testing; 7) Product Revision; and 8) Usage Tests. The stages carried out in this study are: Phase 1, namely the potential and problems carried out with the aim of finding out the problems in the field about learning models that can improve six aspects of early childhood development. This stage was carried out in six PAUD institutions with observation, interview and documentation methods. Stage 2 is gathering information/data, taken from three sources, namely learning implementation plans (RPP), teaching teachers, and students in six PAUD 5-6 year age groups. Stage 3 is product design, namely developing an existing learning model into a science-based learning model. The purpose of developing this learning model is to improve six aspects of early childhood development. The basis of the development of this science-based learning model is the curriculum 2013, several references from science learning books, learning material taken from daily activities of students, and traditional games that are easily played by early childhood. The observation results from the teacher as a user based on the questionnaire are as follows: 1) PAUD Mutiara Ilmu Samarinda received an average of 4.2 with the category "Good"; 2) PAUD Palapa Samarinda gets an average of 5.0 with the category "Very Good"; 3) RA An Nur Al Ikhlas Kutai Kertanegara received an average of 4.2 with the category "Good"; 4) PAUD Media Sandika Balikpapan gets an average of 5.0 with the category "Very Good"; 5) PAUDBalikpapan Anggrek I  received an average of 4.6 with the category "Very Good"; 6) Anggrek II ECD gets an average of 4.5 in the category of "Very Good". So that the observations from the teacher as a user based on the questionnaire as a whole got an average of 4.6 with the category "Very Good". Based on all of the above descriptions, the results of student and teacher testing as instructors are known to be effective science-based learning models used to improve six aspects of early childhood development.